Wicksellian Rules and the Taylor Principle: Some Practical Implications - Caputo-Galarce, R (Blackwell Publishing Ltd, 2020)
In this paper, we derive and compare the determinacy regions of price-level targeting rules (Wicksellian rules) and Taylor rules in a standard New Keynesian model. We conclude that Wicksellian rules do not require the Taylor principle to hold in order to induce determinacy. Our results have two implications. First, in a univariate setting, the estimation of simple Taylor rules when the true rule is Wicksellian can lead to the erroneous conclusion that the equilibrium is indeterminate. Second, indeterminacy is ruled out when using system-based methods, but it can be concluded that the central bank is less averse to inflation movements than it actually is. © The editors of The Scandinavian Journal of Economics 2018.